2013
DOI: 10.1590/s1806-37132013000600002
|View full text |Cite
|
Sign up to set email alerts
|

Metformin synergistically enhances antiproliferative effects of cisplatin and etoposide in NCI-H460 human lung cancer cells

Abstract: OBJECTIVE: To test the effectiveness of combining conventional antineoplastic drugs (cisplatin and etoposide) with metformin in the treatment of non-small cell lung cancer in the NCI-H460 cell line, in order to develop new therapeutic options with high efficacy and low toxicity. METHODS: We used the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and calculated the combination index for the drugs studied. RESULTS: We found that the use of metformin as monotherapy reduced the metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 20 publications
1
25
0
2
Order By: Relevance
“…Through the detection of cell apoptosis markers Bcl‐2 and Bax in the treated or control groups and a data comparison between the different groups, the synergistic effects between metformin and pemetrexed on NSCLC or sensitization effect of metformin to chemotherapy were verified again. Our data demonstrated the relationship between metformin and pemetrexed in treating NSCLC in vitro, which is consistent with the previous findings regarding metformin and other chemicals, such as cisplatin or etoposide .…”
Section: Discussionsupporting
confidence: 92%
“…Through the detection of cell apoptosis markers Bcl‐2 and Bax in the treated or control groups and a data comparison between the different groups, the synergistic effects between metformin and pemetrexed on NSCLC or sensitization effect of metformin to chemotherapy were verified again. Our data demonstrated the relationship between metformin and pemetrexed in treating NSCLC in vitro, which is consistent with the previous findings regarding metformin and other chemicals, such as cisplatin or etoposide .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it recently gained increasing interest from the medical community due to its potential antitumor effects [ 9 ]. A growing body of data suggests that metformin may elicit antitumor effects alone [ 9 , 10 ] or synergistically improve the response of radiotherapy or chemotherapy [ 9 , 11 , 12 ]. However, recent studies showed an unexpected antagonistic effect of metformin on the cytotoxicity of DDP in vitro [ 13 , 14 ], suggesting that caution should be taken when considering metformin for the treatment of diabetic cancer patients receiving DDP or as a potential adjuvant in DDP-based chemotherapeutic regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a preclinical study, metformin sensitized lung cancer cells to ionizing radiation, which led to an increased response to radiotherapy [41]. Metformin has also been found to exhibit synergistic effects with chemotherapy and target therapy and has thus been studied as an adjuvant treatment for lung cancer [37,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%